Chronic venous insufficiency – pathogenesis, diagnosis and pharmacological treatment. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part II - Narbutt, Joanna; Bowszyc-Dmochowska, Monika; Kapińska-Mrowiecka, Monika; Kaszuba, Andrzej; Krasowska, Dorota; Kręcisz, Beata; Lesiak, Aleksandra; Lis-Święty, Anna; Maj, Joanna; Nowicki, Roman; Owczarek, Witold; Placek, Waldemar; et al. (Dermatology Review/Przegląd Dermatologiczny, 2018)
Chronic venous insufficiency is an important clinical problem in daily dermatological practice. The second part of the Recommendations describes in detail aspects related to the pathophysiology of the venous system. Basic information about the diagnosis and therapy of chronic venous insufficiency is also provided, with a special focus on patients’ lifestyle changes, compression therapy and pharmacological treatment.